2021
DOI: 10.3389/fbuil.2021.672102
|View full text |Cite
|
Sign up to set email alerts
|

Active Botanical Biofiltration in Built Environment to Maintain Indoor Air Quality

Abstract: The implementation of sustainable solutions for maintaining indoor air quality has become a particular concern to the building community. Research on green technologies for indoor air has highlighted the potential of active botanical biofiltration (ABB) systems, where the air is circulated through the plant root zone as well as the growing medium for maximum phytoremediation effect. ABB has been found beneficial for pollutant removal along with the potential for increasing humidity and air cooling. Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Due to rapid urbanization globally, in the past few decades, staying in different indoor environments has become a common practice among the urban population (Mannan and Al-Ghamdi, 2021). However, staying in an indoor environment for a longer period of time with poor indoor air quality can pose a serious threat to human health (Tham et al 2016).…”
Section: Methods For Phytoremediation Of Indoor Airmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to rapid urbanization globally, in the past few decades, staying in different indoor environments has become a common practice among the urban population (Mannan and Al-Ghamdi, 2021). However, staying in an indoor environment for a longer period of time with poor indoor air quality can pose a serious threat to human health (Tham et al 2016).…”
Section: Methods For Phytoremediation Of Indoor Airmentioning
confidence: 99%
“…There are approximately 200 different types of air pollutants in ecosystems that can harm the human respiratory system, which is regarded as the world's greatest environmental health risk (Orellano et al 2020;Han et al 2022). Globally, more than 80-90% of people spend their entire lives indoors, in places like schools, educational institutes, colleges, offices, homes, and other commercial structures (Mannan and Al-Ghamdi 2021). On a global scale, studies have revealed that air pollution is responsible for one out of every ten deaths (Gonzalez-Martin et al 2020).…”
Section: Air Pollutionmentioning
confidence: 99%
“…The primary removal mechanism of VOCs by active botanical biofilters is the delivery of a contaminated airstream to the rhizospheric bacteria hosted by the plant through the use of mechanised components (Deng and Deng 2018 ; Mannan and Al-Ghamdi 2021 ). This allows for an increase in the delivery rate of pollutants to the rhizosphere, which is largely believed to drive the phytoremediation process termed rhizodegradation (Torpy et al 2015 ).…”
Section: Plants As a Phytoremediation Technologymentioning
confidence: 99%
“…The authors [65] studied the system over 300 days. Satisfactory efficiency was found to remove formaldehyde and toluene (90 % and more than 33 %, respectively, during the first four days).…”
Section: Technology Of Active "Green" Structures For Indoor Air Purif...mentioning
confidence: 99%
“…The same authors [65] also conducted many studies in laboratory conditions. The efficiency of the system in removing PM was evaluated exclusively in a static chamber, where a general observation recorded that the efficiency of PM removal increased with an increase in the airflow rate.…”
Section: Technology Of Active "Green" Structures For Indoor Air Purif...mentioning
confidence: 99%